Mumarasah Extracurricular Learning and Its Effectiveness in Improving Arabic Speaking Skills - Zulfa Amalia Wahidah; Faiq Ilham Rosyadi (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Purpose - This study aims to determine the implementation of the extracurricular mumārasah program at MA Ali Maksum and the extent to which the extracurricular mumārasah in improving Arabic speaking skills. Design/methodology/approach - This research is quantitative descriptive. To collect data, researchers used a questionnaire. To test the effectiveness of mumārasah extracurricular, the authors used pre-test and post-test tests. Findings - The study results indicate that implementing extracurricular activities for mumārasah runs with a learning model using direct methods, small group discussions, role-playing, memorizing dialogue, role-playing, and group conversations. However, the extracurricular implementation is considered ineffective due to several factors, such as the unformed lughāwiyyah and the low discipline level. The mumārasah extracurricular effectiveness test results in improving students' Arabic speaking skills proved effective with a significant increase, namely, 3.388. Originality/value - Extracurricular mumārasah teacher also expected to make rules or agreements discipline with students in class individual, so that students are more disciplined and follow classes with regular. Paper type – Research paper